Comparisonal Analysis of Health Level Conventional Bank in Indonesia before and during the Covid-19 Pandemic with Using the RGEC Method - Suripto Suripto; Victor Prasetya; Retno Cahyaningati (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2022)
The purpose of this study is to analyze whether there is a difference in the health of conventional banks before and during the COVID-19 pandemic using the RGEC approach.This research is a comparative research, to compare the similarities and differences of two or more facts and properties of the object under study based on a certain frame of mind. The data analysis technique in this study is to use the Independent T-Test test.The results showed that the NPL variable had a significant difference with sig. (2-tailed) value 0.00 <0.05, the LDR variable has a significant difference with the sig value. (2-tailed) value 0.00 < 0.05, the ROA variable has a significant difference with the sig value. (2-tailed) of 0.02 < 0.05 And the CAR also has a difference. Which is significant with sig. (2-tailed) value 0.01 <0.05, while the GCG variable does not have a significant difference with sig. (2-tailed) the value is 0.363 > 0.05, and the NIM variable does not have a significant difference with sig. (2-tailed) value 0.058 > 0.05.